DRUG-seq for miniaturized high-throughput transcriptome profiling in drug discovery - Chaoyang Ye (Nature Portfolio, 2018)
RNA-seq is a powerful tool to investigate how drugs affect the transcriptome but library construction can be costly. Here the authors introduce DRUG-seq, an automated platform for high-throughput transcriptome profiling.